Global epidemic of diabetes, growing burden of young-onset diabetes, and regional perspective - Siddiqui, Md Nazrul Islam (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Abstract not available J Assoc Clin Endocrinol Diabetol Bangladesh, January 2025;4(1): 1-3